Comparative Income Combination of Farming and Cattle Bali in Palangga Subdistrict South Konawe Regency - La Ode Arsad Sani; Harapin Hafid; Laode Muh Munadi; Ahmad Doni (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The research aims to determine the income of cattle business combined with horticultural farming and palawija in April-June 2020 in Palangga District, South Konawe Regency. The location determination method is purposive, where there are farmers with horticulture and palawija farming. Respondents in the study were 40 farmers. The data is analyzed qualitatively and quantitatively to compare cattle income, horticulture, and palawija. The results showed that the average income of livestock business amounted to Rp. 8.779.500/year and horticultural and palawija farming Rp. 18.889.950/year, Bali cattle business income combined horticultural farming of Rp. 20.931.200/year and Bali cattle business combined palawija farming of Rp. 6.738.250/year.